ANALISIS PENGGUNAAN PARTNERSHIP (SYIRKAH) PADA LEMBAGA DAN MANAJEMEN KEUANGAN SYARIAH - JUM'AN (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
Indonesia has a fairly high percentage of Muslim, therefore we as Indonesian should know about the use of this syirkah. By knowing its use by Muslim in Indonesia, it can make syirkah a new tool in making profits or doing business and business. And with this syirkah, businessmen or entrepreneur can find out how to avoid losses. This Research uses a qualitative method. Through this method is expected to be able to analyze the phenomenon researched. This qualitative research is only describing and spell out to find in the field without requiring a hypothesis. Implementation of musyarakah in Islamic Financial Institutions can be found in project financing, venture capital, musyarakah mutanaqisah financing, and sharia bonds or sukuk. The Financing Project of Musyarakah is usually applied to project financing where the customer and the bank both provide funds to finance the project, and after the project is completed the customer return the funds together with the agreed profit sharing for the bank. keywords : Syirkah; Capital Venture, Financing Project.